Performance Evaluation of Textile Industries in Bangladesh: An Empirical Study - Uddin, Md Helal; Rahman, Muhammad Mahbubur (Review of Industrial Engineering Letters, 2015)
The objective of the study is to measure the performance of Textile Industries in Bangladesh for the sake of stakeholders to make economic decision. For this study, eight trend equations have been tested for different activities of the Textile industries and Square of correlation coefficient (r2) has also been tested for all trend equations. It is observed that all selected Textile industries are not able to achieve a stable growth, Square of correlation coefficient (r2) is positive in many cases above 0.90.The study also found that 97% of the respondents are agree & strongly agree that there are two main problems of textile companies of Bangladesh, one is huge tax rate another is Inadequate training facilities. The study recommended that if the government can reduce tax rate on imported goods for Textile industries then the textile industry will be more benefited.